Andrew's brain : a novel - Doctorow, E. L., 1931- (New York : Random House, 2014)
Speaking from an unknown place and to an unknown interlocutor, Andrew is thinking, Andrew is talking, Andrew is telling the story of his life, his loves, and the tragedies that have led him to this place and point in time. And as he confesses, peeling back the layers of his strange story, we are led to question what we know about truth and memory, brain and mind, personality and fate, about one another and ourselves.
Keywords: Neuroscientists -- Fiction; Brain -- Fiction; Identity (Psychology) -- Fiction; Interpersonal relations -- Fiction; Loss (Psychology) -- Fiction; Memory -- Fiction